Pelatihan Pembuatan Perangkat Ajar Pada Guru-Guru Taman Kanak-Kanak Dan Sekolah Dasar - Liza Fitriana; Dody Hidayat; D David; R Ramli (LPPM STIKOM Tunas Bangsa, 2022)
Teaching is an activity carried out by a teacher in transferring knowledge to students. Generally, the teaching and learning process is conducted in a room or class where there are teachers and students inside which are usually called face-to-face or offline meetings. The problem came when Covid-19 was determined to be an epidemic disease in the world so the Government did not allow the teaching and learning process to be conducted offline. This means all teaching and learning processes must be conducted online. For this reason, the ability of teachers to make teaching media that will be presented online must be upgraded in order to make the subject that should be transferred to students can be presented in a good and interesting manner. For this reason, we, the Universitas Harapan Medan Service Team, conducted a Training on Making Teaching Media for Kindergarten and Elementary School Teachers.